Hypoglycemic Effects of Polyphenol Complexes from Bilberry Leaves and Fruits Sorbed on Brown Buckwheat Flour -- Experimental Evaluation and Prospects of Use - Petrov, Nikita; Sidorova, Yulia; Kochetkova, Alla; Mazo, Vladimir (KnE Life Sciences, 2022)
The effects of plant polyphenols on carbohydrate and/or lipid metabolism disorders have wide experimental and clinical justification; however, their effects are limited due to low bioavailability. Thus, the development of technological approaches enhancing their effectiveness and stability is relevant.The aim of this work was to evaluatein vivothe effects of polyphenols from bilberry leaves and fruits, sorbed on the brown buckwheat flour, on C57Bl/6c mice with carbohydrate and lipid metabolism disorders. We assessed in vivothe effect of a food matrix (FM1: bilberry leaf polyphenols sorbed on brown buckwheat flour) on C57Bl/6c mice with induced carbohydrate and lipid metabolism disorders. The aim of the second experiment was to evaluate the effectiveness of prolonged prophylactic consumption of another food matrix (FM2: billberry fruit polyphenols, sorbed on brown buckwheat flour) by C57Bl/6c micewith induced carbohydrate and lipid metabolism disorders. Technological approaches were developed and pilot batches of the food matrices FM1 and FM2were obtained. According to the in vivo testing, a significant decrease in the glucose levels and normalization of glucose tolerance and insulin sensitivity were found in animals treated with FM1. When assessing the in vivo effects of FM2, the hypoglycemic effect of bilberry fruit polyphenols in the composition of the matrix was established. The results of these studies can be used to justify the testing of the developed matrices in a clinical setting and using them as functional food ingredients for preventative nutrition in cases of carbohydrate metabolism disorders. Keywords: polyphenols, food matrix, functional food ingredient, carbohydrate metabolism, lipid metabolism